2017
DOI: 10.1093/hmg/ddw385
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte development and CNS myelination are unaffected in a mouse model of severe spinal muscular atrophy

Abstract: The childhood neurodegenerative disease spinal muscular atrophy (SMA) is caused by loss-of-function mutations or deletions in the Survival Motor Neuron 1 (SMN1) gene resulting in insufficient levels of survival motor neuron (SMN) protein. Classically considered a motor neuron disease, increasing evidence now supports SMA as a multi-system disorder with phenotypes discovered in cortical neuron, astrocyte, and Schwann cell function within the nervous system. In this study, we sought to determine whether Smn was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Ddx20 -null mice and Smn1- null mice die at different stages, with Ddx20 -null embryos demonstrating lethality as early as the four-cell stage [ 14 ], whereas Smn1 -null embryos show lethality after the morula stage [ 34 ]. Furthermore, SMA model mice ( Smn1 −/− ; SMN2 mice) do not demonstrate changes in OPC proliferation and/or oligodendrocyte differentiation [ 35 ]. These differences suggest that Ddx20 plays other roles, in addition to acting as a component of the SMN complex.…”
Section: Discussionmentioning
confidence: 99%
“…Ddx20 -null mice and Smn1- null mice die at different stages, with Ddx20 -null embryos demonstrating lethality as early as the four-cell stage [ 14 ], whereas Smn1 -null embryos show lethality after the morula stage [ 34 ]. Furthermore, SMA model mice ( Smn1 −/− ; SMN2 mice) do not demonstrate changes in OPC proliferation and/or oligodendrocyte differentiation [ 35 ]. These differences suggest that Ddx20 plays other roles, in addition to acting as a component of the SMN complex.…”
Section: Discussionmentioning
confidence: 99%
“…Whether OL lineages are involved in SMA pathogenesis is controversial. O'Meara et al found that OL growth, migration, differentiation, and myelination were not affected in severe SMA mice (Smn −/− , SMN2 +/+ ) [82]. However, Kazuki Ohuchi et al found that the OL lineage was impaired in Δ7 SMA mice [83].…”
Section: Discussionmentioning
confidence: 99%
“…We detected dysregulation of myelin gene splicing, which was similar to that in quaking viable ( qk v ) mice, classical demyelination mutants (Wu et al, 2002). Although oligodendrocyte development and CNS myelination were unaffected in SMA model mice ( Smn1 −/− ; SMN2 mice) (O'Meara et al, 2017), SMN2 may be able to compensate for the loss of Smn1 function. In mouse genome, only one Smn gene, Smn1 , is encoded, and Smn1 KO mice show early lethality at the peri‐implantation stage (Schrank et al, 1997).…”
Section: Discussionmentioning
confidence: 99%